(untitled) (Colombia Medica, 2011)
Introduction: The concept of workload has been used by nursing with multiple meanings. Among them, we have considered patient dependency and nursing intensity. We propose to add to this understanding that workloads are biopsychic processes with effects on the worker’s body. Development: We discuss this theoretical concept based on the Latin American contribution and the importance of theory in the conceptual field. Final reflection: This discussion provides other theoretical ways to operate this concept in areas of research, focusing on the worker’s health. Also, this concept in nursing research helps to further study the work process and its relationship with health to analyze the contribution of each component of this in the health nursing workers.